PENGARUH PERENCANAAN SUMBER DAYA MANUSIA TERHADAP KINERJA PEGAWAI: Studi pada Mom N Baby SPA Al-Fatihana kota Kediri - Ari Fitriana, Indra; Utami Hanggondosari, Sri; Dina, Nur; Hariono, Jefri (Universitas Pawyatan Daha, 2023)
The implementation of the stateful planning of this new business is not only in the planning of service products and marketing but also in its operational management, especially in the management of its human resources. The population in this study was taken from the total number of employees at Mom N Baby SPA as many as 18 people. Human Resource Planning has a significant effect on employee performance and on improving employee performance at Al Fatih Mom N Baby SPA And Al Fatih Mom N Baby SPA Resource Planning.